Triorchidism at orchidopexy: a case report - Athwal Sharan; Tailor Jignesh; Lakhoo Kokila (Journal of Medical Case Reports, 2008)
Abstract Introduction Polyorchidism is defined as the presence of more than two testes. The management of this rare condition is still debatable, particularly when it is an incidental finding at surgery. Case presentation We present the case of an 8-year-old boy with triorchidism found incidentally during an elective orchidopexy. This supernumerary, ectopic and atrophic testis was removed to avoid an increased risk of malignancy. Conclusion Risk of malignancy justifies the removal of an atrophic and ectopic testis in triorchidism. However, it would appear safe to preserve a viable intrascrotal supernumerary testis found incidentally at surgery provided that the patient is followed up in the long term.